Assessment of the potential of selected adsorbents for use in small-scale systems for the removal of uranium from mine-impacted water - Mabape, Kgaugelo Ishmael Smiley (My University, 2017)
The tailoring of zeolites surface properties using organic functionalising agents displaying higher binding affinity for metal ions is a widely explored approach for water treatment. In this study, amine functionalised zeolites and phosphate functionalised zeolites were separately synthesised from similar natural zeolite precursors using reflux methods. The surface composition and morphological elucidations were achieved by characterising the adsorbents using Fourier Transform Infra-red spectroscopy (FTIR), thermogravimetric analysis (TGA), Zeta potential, Point of zero charge (pHPZC), and the Brunauer, Emmett and Teller analysis (BET). In case study 5.1, the sorption mechanisms of the uranyl ion onto amine functionalised zeolites (AMZ), activated carbon (AC) and natural zeolite (NZ) were studied as function of various environmental batch parameters. There was effective adsorption when uranium existed as uranyl ions: UO22+ and UO2OH+. The data fitted numerous kinetic and isotherm models suggesting that the equilibrium mechanisms were characteristic of a combination of chemisorption and physisorption for these three adsorbents. The Dubinin-Radushkevich (DR) model did not fit the data and therefore the energy values derived from it were not used to predict the mechanisms involved. However, the thermodynamic evaluations of parameters ∆H, ΔG and ∆S° showed that equilibrium mechanisms were exothermically, randomly and spontaneously favoured for all adsorbents at temperatures ranging between 22 and 40oC. The adsorption capacity of 0.452 mg g-1 was achieved at pH 3 by 500 mg AC dosage using 20 mL volume of 10 mg L-1 uranyl ion solution after equilibrating for 6 h within the temperature ranges of 22 to 30oC. Under the same conditions of sorbent dosage of 500 mg, uranyl solution volume of 20 mL and 10 mg L-1 U(VI) solution concentration, the maximum adsorption capacity of 0.506 mg g-1 for NZ and 0.480 mg g-1 for AMZ were both achieved at pH 4 after equilibration time of 21 h and 6 h with the optimum temperature range of 22 to 30oC, respectively. The model results predict that intraparticle diffusion thorough pores decreased in the order AC ˃ NZ ˃ AMZ while estimating that chemisorption occurred in a reverse order. On the basis of the modelled data, it was deduced that amine functionalisation of natural zeolites improves their chemisorption capability for uranyl ion and can therefore be used as a cost efficient adsorbent for small-scale remediation of contaminated aquatic systems. In another case study 5.2, the surface properties of successfully prepared aminomethyl phosphonic acid functionalised natural zeolite (APZ) were compared to those of commercial silica polyamine composites (SPC) for uranium uptake in batch aqueous solutions. The FTIR spectrum revealed that (3-aminotrimethyl) phosphonic acid functional groups were successfully grafted onto natural zeolite. The TGA analysis showed that the APZ had higher thermal stability and fewer active sites compared to SPC. The optimum adsorption capacity (qe) of 49 mg g-1 and 44 mg g-1 uranium was achieved using 25 mg SPC and 100 mg APZ, respectively at pH 4, 25oC after 1 and 6 h equilibrating time. The data best fitted the pseudo second-order kinetic model and Freundlich isotherm model. The thermodynamic studies showed that adsorption occurred chemically and exothermically for both APZ and SPC. The overall selectivity order for APZ was; Na ˃ Mn ≥ U ˃ Ca ˃ Fe and for SPC was; Fe ˃ Mn ≥ Ca ˃ U˃ Na. The findings showed that phosphate- and amine-functionalised zeolite bind strongly to uranium compared to the unmodified natural zeolite and other conventional adsorbents such as activated carbon. Their selectivity for this element was commendable. With further improvements in the synthetic protocols e.g. by using microwave-based methods, it should be possible to obtain functionalised zeolite that has superior properties to SPC.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Masters of Science, 2017
Keywords: Groundwater--Purification--Uranium removal; Acid mine drainage; Water--Purification